Land cover mapping of the Igarapé do Dez River Basin, Ji-Paraná, Rondônia, Brazil, Western Amazon (Research, Society and Development, 2020)
The state of Rondônia started the occupation process in the 1960s, at the incentive of the federal government based on colonization plans. The settlements were largely responsible for the changes in the natural landscape, transforming areas of forests into areas of agriculture and pasture mainly. INPE reported that in the period from 2018 to 2019, there was an increase of about 50% of deforestation in relation to the period from 2017 to 2018. Thus, studies of hydrographic basins have been intensified in view of the speed of degradation of water resources and through land use and occupation, whether for agricultural, livestock, rural or urban settlements. The present work aimed to map the soil cover of the Igarapé dos Dez hydrographic basin, located in Ji-Paraná, in the State of Rondônia. The percentage of deforestation that occurred in the 30-year period was analyzed and for the analysis of deforestation, images from the Landsat 5 satellites from 1988, 1998 and 2008 and Landsat 8 from 2018 were used.